Long‐term warming destabilizes aquatic ecosystems through weakening biodiversity‐mediated causal networks - Chun‐Wei Chang; Hao Ye; Takeshi Miki; Ethan R. Deyle; Sami Souissi; Orlane Anneville; Rita Adrian; Yin‐Ru Chiang; Satoshi Ichise; Michio Kumagai; Shin‐ichiro S. Matsuzaki; Fuh‐Kwo Shiah; et al. (Global Change Biology, 2020)
Understanding how ecosystems will respond to climate changes requires unravelling the network of functional responses and feedbacks among biodiversity, physicochemical environments, and productivity. These ecosystem components not only change over time but also interact with each other. Therefore, investigation of individual relationships may give limited insights into their interdependencies and limit ability to predict future ecosystem states. We address this problem by analyzing long‐term (16–39 years) time series data from 10 aquatic ecosystems and using convergent cross mapping (CCM) to quantify the causal networks linking phytoplankton species richness, biomass, and physicochemical factors. We determined that individual quantities (e.g., total species richness or nutrients) were not significant predictors of ecosystem stability (quantified as long‐term fluctuation of phytoplankton biomass); rather, the integrated causal pathway in the ecosystem network, composed of the interactions among species richness, nutrient cycling, and phytoplankton biomass, was the best predictor of stability. Furthermore, systems that experienced stronger warming over time had both weakened causal interactions and larger fluctuations. Thus, rather than thinking in terms of separate factors, a more holistic network view, that causally links species richness and the other ecosystem components, is required to understand and predict climate impacts on the temporal stability of aquatic ecosystems.